Ma‘had al-Juntūr Bayna al-Tajdīd wa al-Taqlīd - Mahrus As'ad (Center for Study of Islam and Society (PPIM) Syarif Hidayatullah State Islamic University, 1996)
Gontor boarding schools founded in 1926 by three brothers scholars commonly known as Trimurti, namely Ahmad Sahal, Zainuddin Fanani, and Zarkasyi. This paper will describe the development of Gontor boarding schools from the beginning has been oriented reform, in contrast with Islamic tradition that tends to traditionalists.DOI: 10.15408/sdi.v3i4.796